Immunoassay of interferon gamma by quartz crystal microbalance biosensor - Pohanka, Miroslav (Talanta, 2020)
Interferon gamma (IFNγ) is a cytokine and an immunochemical marker that can be used for revealing of infectious diseases and especially for distinguishing of viral and some types of bacterial infections. Blood tests for IFNγ are typically based on immunoassays like Enzyme-Linked Immunosorbent Assay (ELISA). In this paper, a biosensor working on the principle of quartz crystal microbalance (QCM) was developed as an alternative to the standard analytical methods for IFNγ. The biosensor contained antibodies against IFNγ immobilized on QCM and also on gold nanoparticles. A sandwich containing QCM, gold nanoparticles and IFNγ was formed and formation of the sandwich caused decrease of oscillation frequency. The assay exerted limit of detection 5.7 pg/ml for a sample sized 50 μl and one measuring cycle was finished within 90 min. The assay by biosensor fully correlated to standard ELISA. In a conclusion, the biosensor appears to be a fully applicable analytical tool for a simple assay of IFNγ. Overall simplicity and no special requirement on staff and equipment are the major advantages of the here presented assay.
Keywords: Cytokine; Humans; zlato; Quartz Crystal Microbalance Techniques; Biosensing Techniques; ELISA; lidé; biosenzitivní techniky; kovové nanočástice; Virus; Infection; křemen; mikrorovnovážné techniky křemenného krystalu; Immunoassay; Bioassay; interferon gama; Macrophage; Gold; Immunosensor; Lymphocyte; Quartz; imunoanalýza; Metal Nanoparticles; Diagnosis; Interferon-gamma; Biosensor